The management of vaginal bleeding in advanced cervical cancer - Olejniczak, Lexie; Zasowska-Nowak, Anna (Medycyna Paliatywna/Palliative Medicine, 2023)
Cervical cancer is the fourth most diagnosed malignancy worldwide. This narrative review aimed to assess various treatment methods for reducing or completely stopping vaginal bleeding, which is one of the most common and alarming complaints reported by women with cervical cancer. The treatment of bleeding depends on its intensity, potential causes (reversible and irreversible), stage of the disease, and prognosis. In advanced-stage patients receiving palliative care, interventional methods such as embolization or surgical ligation of internal iliac vessels, or epigastric or uterine arteries are usually not possible due to the patient’s poor general condition. The treatment of choice is conservative therapy, which includes the performance of vaginal tamponade (usually using sterile gauze, haemostatic gauze, or cellulose sponges), the use of anti-haemorrhagic drugs (tranexamic acid, vitamin K), and, in selected clinical situations, palliative radiotherapy. The literature on the subject points to reports on the effectiveness of topical 4% formalin solution, Mohs paste, Monsel’s solution, thrombin, or epinephrine in inhibiting vaginal bleeding. However, these are not supported by data from randomized clinical trials. Data available in databases on the alleviation of cervical vaginal bleeding are limited, so there is a need for further clinical research on this topic.